Rumors : a Luxe Novel - Godbersen, Anna (New York : HarperCollins Publishers, 2008)
As rumors continue about the untimely demise of Elizabeth Holland, an outwardly stricken Penelope Hayes determines to use any means necessary to claim her friend's pre-eminent place in 1899 Manhattan society and to get and keep the attentions of Elizabeth's former fiancé, the wealthy Henry Schoonmaker.
Sequel to: The Luxe.
Sequel: Envy.
Accelerated Reader AR
Keywords: Young adult fiction